Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019 41st Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2019
DOI: 10.1109/embc.2019.8856882
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic Sensor-based Shape Sensing Approach for Flexible Manipulators

Abstract: This paper presents a novel two-axis shape sensor based on optical optoelectronic sensors and integrated with a flexible manipulator arm to measure the overall shape of the robotic arm. The disc-shape bio-compatible sensor presented here can be embedded as a sensing system into flexible manipulators and is applicable to the geometry of its structure and to the structure of any other similar multi-segment robotic manipulator. Design and calibration procedures of the device are introduced: experimental results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The technique offers a simple, small, biocompatible system that does not intrinsically depend on curvature limiting properties such as strain or temperature and can be adapted to work with different continuum robotic structures. Koh et al [1] showed early stages of this work, presenting a shape sensing method using optoelectronic sensors integrated within 3-plates of a tendon actuated flexible robot (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The technique offers a simple, small, biocompatible system that does not intrinsically depend on curvature limiting properties such as strain or temperature and can be adapted to work with different continuum robotic structures. Koh et al [1] showed early stages of this work, presenting a shape sensing method using optoelectronic sensors integrated within 3-plates of a tendon actuated flexible robot (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The gyroscopes and accelerometers provide the orientation of the object in 3D for visualization purposes. It is a low-cost technique using mass-produced sensors and data acquisition tools available in the market (Benjamin Koh et al , 2019). SensorTape is a commercially successful optoelectronic-based shape sensor which uses printed electronics on a narrow ribbon type sheet to accommodate all the LED sources such as light detectors and conducting lines (Dementyev et al , 2015).…”
Section: Review Of Shape Sensing Methods and Fiber Optics Based Shape Sensingmentioning
confidence: 99%
“…Several successful studies using the optoelectronic sensor have been reported for sensing shape information. Benjamin et al employed three photoelectric sensing elements (QRE1113, Fairchild Semiconductor Corp.) to estimate the shape of a snake-like flexible manipulator [32], and Dalia et al integrated them into the joints of a robot hand finger to measure its shapes [33]. In the former case, although the concept and idea were novel, the pose sensing accuracy was not precisely guaranteed.…”
Section: Introductionmentioning
confidence: 99%